أحكام التحفّل والاحتفال عند النساء في الزواج - رابح, أسماء (University of Eloued جامعة الوادي, 2020)
" موضوع البحث موسوم ب: ""أحكام التحفل والاحتفال عند النساء عند الزواج"" دراسة جمع فقهية، والاشكاليةالرئيسية لهذه الدراسة تتمحور حول الاحكام الشرعية المتعلقة بما شاع عند النساء في حفلات الزواج وذالك لأنه يكثر مايتلبس بالمرأة وماتزاوله من تحضيرات وحفل الزواج اكثر المناسبات تحفلا بشتى أنواع الزينة وتتنوع فيه مراسيم الاحتفال، وهذا الموضوع مدروس في مبحثين خصص المبحث الاول لاحكام تحفل النساء في يوم الزواج استعدادا للحفل، اما المبحث الثاني فهو لاحكام عادات احتفال النساء، ومن اهم النتائج المتوصل إليها بعد البحث ان الاصل في عادات زينة المرأة واحتفالها بالزواج الاباحة لان الأصل في العادات الاباحة إلا ان توفر المحاديث والمحظورات فيها يبطلها، ولهذا لابد لهذه العادات أن تحكم وتضبط هذه العادات وفق الشرع، وختم البحث بتوصية يحث فيها عن الوقوف على أحكام التحفل والاحتفال الصحيحة والعناية والاهتمام بأحكام العادات الحديثة والجديدة في ذلك ق" The title of the thesis is: “Rulings on marriage and celebration among women on the day of marriage: a study of jurisprudential collection.” The main problem of this study revolves around the Sharia rulings related to what is common among women in the marriage celebration and in who they do in the marriage itself. The adornment and the variety of ceremony ceremonies, and this topic is studied in two parts: The first part is devoted to the provisions of the marriage ceremony of women in preparation for the ceremony, and the second part is the rules of the customs in the celebration of women, and one of the most important results reached after the research is that the basic principle in the customs of a woman’s adornment and celebration of marriage is permissibility because The basic principle in customs is permissibility, but the availability of prohibitions in them nullifies them, and this is why these customs must be governed and controlled according to the Sharia. The master's thesis concluded with a recommendation in which it urges us to study the correct rulings of partying and celebration, and to take care of the rules of modern and new customs in that before living with them and getting used to them."بل التعايش معها وتعودها. "
مذكرة ماستر تخصص فقه مقارن واصوله
Keywords: أحكام، تحفل، احتفال، نساء; rulings. accessories. celebration. women